ANALISIS PEMBELAJARAN IPAS DITINJAU DARI PERENCANAAN PEMBELAJARAN KELAS IV SDN 51 SUNGAI RAYA - Zelya Lespenia; Dessy Setyowati; Suriyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze science learning in terms of lesson planning. The background of this research is based on an analysis of teaching modules, including the suitability of learning objectives, material selection, strategies, methods, media, and assessment instruments used by teachers. This study used a qualitative approach with descriptive methods. The subjects were fourth-grade teachers at SDN 51 Sungai Raya. Data collection techniques were conducted through analysis of teaching modules and documentation of the learning tools used by teachers. The results show that the science learning planning has covered the main components, but there are still several weaknesses, such as a lack of variety in learning methods and limited media utilization. In addition, the assessment planning has not fully accommodated students' science process skills. This study concludes that the quality of science learning can be improved if teachers are able to develop learning plans that are more systematic, contextual, and oriented towards skills development.